EFFECTS OF MICROSTRUCTURE ON THE LARGE COMPRESSION BEHAVIOR OF RUBBER FOAMS - FAN ZhiGeng; CHEN ChangQing; HU WenJun; WAN Qiang (Jixie qiangdu)
As a type of typical cellular foams,the macro-mechanical performances of rubber foams are mainly determined by its micro-structure and cell material properties.In the work reported here,several two dimensional（ 2D） finite element（ FE）models having regularly and randomly arranged elliptical and circular cells were constructed.The effects of cell shapes,cell distributing,and porosities on the hyperelastic large compressive deformations of rubber foams were explored.Obtained FE analysis results show that the compressive stress-strain curves of rubber foams present three deforming regions.The compressive stress-strain curves of circular cell models have longer plateau stage than those of elliptical cell models,and circular cell models have more steady mechanical performances than elliptical cell models do.If worked as shockproof cushions,circular cell structures are thus better than elliptical cell structures.